Complexities associated with nucleation of water and ice from jet fuel in aircraft fuel systems: A critical review - Ugbeh-Johnson, Judith; Carpenter, Mark; Williams, Colleen; Pons, Jean-François; McLaren, Dan (Elsevier, 2022)
The contamination and behaviour of water in aircraft fuel systems remains a significant global research interest following several aircraft incidents. To engineer a solution to the problem of icing in jet fuel, it is crucial to precisely identify the conditions and features that may exacerbate this phenomenon. This review will aid prospective researchers to identify work that has been done and work that is yet to be available for future study. In this review, conclusive data integrating a wide range of literature and also providing an in-depth description of the factors that influence the behaviour of trace water, ice formation in jet fuels was carefully summarised. On investigational studies, it was discovered that to date, no work is available that studies the impact of sustainable jet fuel and its blends on ice formation, size and frequency distribution of dispersed water droplets in aircraft fuel systems. Findings from comparative studies also reveal that surfaces will have an essential role in the growth pattern of ice in aircraft fuel systems. Furthermore, findings show that supercooled water droplets with sizes greater than or equal to 5 µm can induce ice accretion. This review identified a common problem with the prominent methods of reporting results as a graphically fitted plot. Subsequently, it proposed that authors of any original technical work provide raw data as supplementary information to allow comprehensibility. The study further offers a system that could help manage the nature of ice in aircraft fuel tank systems—making it readily available and accessible.
Keywords: Ice accretion; Fuel systems; Aviation fuel; Alternative fuel; Water-solubility; Sustainable aviation fuel; Synthetic aviation fuel